Menjaga Warisan Pengetahuan Tradisional: Kajian Etnobotani Tumbuhan Obat Keluarga (TOGA) di Desa Sekarpuro Kabupaten Malang - Nabila Aurelia Pramudita; Fanny Maulidiya Widjayanti; Ajeng Diah Rahmindianti; Fahrul Ghani Muhaimin; Heni Refdiana; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Susriyati Mahanal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Community knowledge about Family Medicinal Plants (TOGA) is an important part of local wisdom that plays a role in maintaining health independently, but has not been optimally documented and shows variations in the level of utilization. This study aims to identify TOGA diversity and analyze its utilization patterns in Sekarpuro Village, Malang Regency. The study used a mixed methods approach with an exploratory sequential design through interviews, observations, documentation, and questionnaires to the community who cultivate and utilize TOGA. Determination of informants and respondents was carried out using purposive sampling and snowball sampling techniques. Data were analyzed qualitatively by referring to the stages of Miles & Huberman, then quantitatively using the ethnobotanical index. The results showed that there were 33 species of medicinal plants from 25 families utilized by the community. The highest Informant Consensus Factor (ICF) value was found in wound diseases (0.90), while Pandanus amaryllifolius had the highest Relative Frequency of Citation (RFC) and Species Use Value (SUV) values, namely 0.46 and 0.98, respectively. The Pandanaceae family demonstrated the highest Family Use Value (FUV) of 0.98. Leaves are the most widely utilized plant part, with a Plant Part Use Value (PPUV) of 50.11%. The Fidelity Level (FL) index is used to assess community tendencies in using a particular plant species to treat specific ailments. The use of traditional medicinal plants (TOGA) in Sekarpuro Village reflects the strong role of local knowledge in supporting traditional healing practices and demonstrates the potential for development, particularly in underutilized plants.